SPHAERIROSTRIS WINDERI N. SP. (ACANTHOCEPHALA: CENTRORHYNCHIDAE) FROM THE HOUSE CROW (CORVUS SPLENDENS: VIEILLOT) (AVES: CORVIDAE) OF BALOCHISTAN, PAKISTAN - A. Khan; R. A. Heckmann (Journal of Animal and Plant Sciences, 2015)
Sphaerirostris winderi n. sp. was obtained from the intestine of the house crow, Corvus splendens Vieillot from Balochistan, Pakistan. The acanthocephalan was present in 1 of 6 examined hosts with 18 worms in the intestine of the infected bird. This new species of Acanthocephala is characterized by a spinous, slender body with a reticular lacunar system. The proboscis is cylindrical, somewhat swollen mid body with 10 to 12 longitudinal rows of 16 hooks each. There are 6 to 8 rows of spines, each row with 14 to 15 spines on the body. Proboscis receptacle is double walled; lemnisci slightly unequal, testes in the anterior trunk; four tubular cement glands; Saefftigen’s pouch and cement glands elongated; bursa is well developed and muscular. Eggs oval without polar prolongations and numerous. Specific differences between S. winderi and other species of the genus include hook and spine number and rows shape and size of the worm and surface pattern of the eggs. Key characteristics and species comparisons are included.
Keywords: Sphaerirostris winderi n. sp.; crow; Corrus splendens; intestine; Balochistan